Sediment Exchange Between the Created Saltmarshes of Living Shorelines and Adjacent Submersed Aquatic Vegetation in the Chesapeake Bay - Vona, Iacopo; Palinkas, Cindy M.; Nardin, William (Frontiers in Marine Science, 2021)
Rising sea levels and increasing frequency of extreme events put coastal communities at serious risk. In response, shoreline armoring for stabilization has been widespread; however, this solution does not take ecological aspects of the coasts into account. The “living shoreline” technique includes coastal ecology by incorporating natural habitat features, such as saltmarshes, into shoreline stabilization. However, impacts of living shorelines to adjacent benthic communities, like submersed aquatic vegetation (SAV), are not clear yet. In particular, while both marshes and SAV trap sediment necessary for their resilience to environmental change, synergies between the communities are not well understood. To help quantify the ecological and protective (shoreline stabilization) aspects of living shorelines, we present modeling results using the Delft3D-SWAN system on sediment transport between the created saltmarshes of the living shorelines and adjacent SAV in a subestuary of Chesapeake Bay. We used a double numerical approach, first to validate deposition measurements made in the field and second to quantify a sediment balance between the two vegetation communities using an idealized model. This model uses the same numerical domain with different wave heights, periods, and basin slope and includes the presence of rip-rap, often used together with marsh plantings in living shorelines, to look at influences of artificial structures on the sediment exchange between the plant communities. Study results indicate lower shear stress, lower erosion rate, and higher deposition rates within the SAV bed compared to the scenario with only marsh, which helps stabilize bottom sediments by making the sediment balance positive (deposition within the two vegetations higher than sediment loss). The presence of rip-rap resulted in a positive sediment balance especially in case of extreme events, where sediment balance was magnified. Overall, SAV helps stabilize bed level and shoreline, and rip-rap works better with extreme conditions, demonstrating how the right combination of natural and built solutions can work well in terms of ecology and coastal protection.